The impact of public scrutiny on executive compensation. Issue 3 (8th July 2019) - Carrothers, Andrew Glen
Abstract : Purpose: This paper aims to examine the impact of public scrutiny on chief executive officer (CEO) compensation at Standard & Poor's (S&P) 500 firms. Design/methodology/approach: This paper uses the unique opportunity provided by the 2008 financial crisis and, in particular, government support and legislated compensation restrictions in the US Department of the Treasury's Troubled Asset Relief Program (TARP). It aggregates monetary and non-monetary executive compensation information from 2006 to 2012, with firm- and manager-level data. It presents univariate summary compensation results and uses multivariate regression analysis to isolate the impact of public scrutiny and legislated compensation restrictions on executive pay. Findings: Overall, the results are consistent, with increased public scrutiny having a lasting impact on perks and temporary impact on wage and legislated compensation restrictions having a temporary impact on wage. Changes in specific perk items provide evidence on which perks firms perceive as excessive and which provide common value. Originality/value: The paper contributes to the discussion of perks as excess by introducing a novel data set of perk compensation at S&P500 firms and by studying how firms choose to alter levels of specific perk items in response to increased public scrutiny and legislated compensation restrictions. The paper contributes to the literature on executive pay as there has been little inquiry into the impact of public scrutiny on compensation. Public scrutiny could be an important source of external governance if firms change behavior in response to explicit and implicit scrutiny costs.